Perlindungan Hukum Notaris Atas Nilai Nominal Transaksi Riil Terhadap Nilai Perhitungan Pajak Yang Melebihi Nilai Transaksi Riil - Syarofi, Syarofi; Fathurrahman, Fathurrahman (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
This study aims to analyze the legal protection of notaries regarding the nominal transaction values in sale and purchase deeds that differ from the BPHTB tax base set by local government authorities. The research focuses on three aspects: the credibility of notaries when transaction values are inconsistent, the responsibility of notaries if the sale and purchase is canceled, and the duties and limits of notaries’ accountability concerning tax value corrections. This research employs a normative qualitative approach using literature review, statutory and regulatory analysis, court decisions, academic literature, and notary professional codes of ethics. Data were analyzed through grammatical, systematic, and teleological legal interpretation, as well as harmonization between notarial and taxation regulations. The findings indicate that: (1) notary credibility is maintained as long as formal authority is exercised and the principle of prudence is applied, although value discrepancies may cause negative perceptions; (2) notaries are not responsible for transaction values when a sale is canceled, provided there is no proven intent or negligence; and (3) the notary’s responsibility is limited to the formal accuracy of the deed and does not include the validation of market or tax value, unless ethical violations or active involvement in value manipulation are proven. The study concludes that legal protection, clear limitation of authority, and application of prudence principles are essential to preserve notarial professionalism while ensuring legal certainty and fiscal compliance.